2008
DOI: 10.1021/jp801445j
|View full text |Cite
|
Sign up to set email alerts
|

Liquid-Phase Structure of Dialkylimidazolium Ionic Liquids from Computer Simulations

Abstract: We present a detailed computational study of the structure of ionic liquids based on the imidazolium cation. Both imidazolium-ring stacking and hydrogen bonding behavior are investigated from radial and spatial orientational distribution functions, as well as orientational correlation functions. The alkyl chain size and anion effect on the liquid structure are provided and discussed. Our results support models for liquid organization comparable to those formulated on the basis of experimental observations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
28
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(35 citation statements)
references
References 63 publications
4
28
0
Order By: Relevance
“…Recently, de Andrade et al [50] performed a detailed analysis of the structure of liquid [emim] [BF 4 ]. According to these simulations the local environment of the cations is characterized by the stacking of [emim] + in the z-direction perpendicular to the imidazolium rings, whereas the counterions are located in the equatorial planes.…”
Section: Accepted M Manuscriptmentioning
confidence: 99%
“…Recently, de Andrade et al [50] performed a detailed analysis of the structure of liquid [emim] [BF 4 ]. According to these simulations the local environment of the cations is characterized by the stacking of [emim] + in the z-direction perpendicular to the imidazolium rings, whereas the counterions are located in the equatorial planes.…”
Section: Accepted M Manuscriptmentioning
confidence: 99%
“…They interpreted the a relaxation to arise possibly from librations of the cations and a slower, sub-a relaxation to arise from relaxation of stacked cation rings. [19] Ludwig et al have carried out FTIR and NMR experiments as well as density functional theory (DFT)-based calculations on the IL [C 2 mim][NTf 2 ] (mim = methylimidazolium; [NTf 2 ] = bis(trifluoromethylsulfonyl)-imide) to study the dynamics of the cation-anion hydrogen bond. [7,20] Moreover, they also studied the validity of StokesEinstein (SE) and Stokes-Einstein-Debye (SED) relations using molecular dynamics (MD) simulations, [21] and found that both the SE and SED relations do not hold good for [C 2 mim][NTf 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…It has been proposed that ionic liquids form three-dimensional structures even in the liquid state because of cation-anion hydrogen bonding and cation-cation ring stacking. [11][12][13] The threedimensional structure may contribute to the modulus of the solutions; if the elasticity due to the network of solvent molecules contributes to the plateau modulus (G N 0 ), then M e,melt is reduced. The aim of this study is to clarify whether or not the network formed by the ionic liquid molecules contributes to G N 0 .…”
Section: Introductionmentioning
confidence: 99%